Anthropometry and body composition of female handball players according to competitive level or the playing position - Milanese, C.; Piscitelli, F.; Lampis, C.; Zancanaro, C. (Journal of Sports Sciences, 2011)
Anthropometry and body composition were investigated in 43 female handball players from the Italian championships, grouped according to their competitive level (elite vs. sub-elite) or their playing position [goalkeeper (n = 7), back (n = 14), wing (n = 18), or pivot (n = 4)]. The anthropometry consisted of several circumferences, lengths, widths, and skinfold measurement at six sites; the regional and total body compositions were assessed by means of dual-energy X-ray absorptiometry (DXA). One-way ANOVA was used for statistical analysis, with a Bonferroni post-hoc test where needed. The results showed that elite players have significantly lower percentages of fat and higher bone mineral content than sub-elite as well as a clear tendency to accrue more lean mass, especially in upper limbs. Overall, the physical characteristics and body composition of handball players in Italy compared unfavourably with those in other countries, suggesting a need for improved selection and training. When playing position was included in the analysis of the whole group of handball players (n = 43) significant differences were found between the stature, mass, body mass index (BMI), several skinfolds, circumferences and lengths, and total body mineral mass, lean mass and fat mass of players in different positions. Post-hoc analysis suggests that players on the wing and in goalkeeper positions differed most from one another. These findings confirm and expand on previous data about the presence of anthropometric differences within playing positions in handball.